Tuberculosis/cryptococcosis co-infection in China between 1965 and 2016 - Wenjie Fang; Lei Zhang; Jia Liu; David W Denning; Ferry Hagen; Weiwei Jiang; Nan Hong; Shuwen Deng; Xia Lei; Danqi Deng; Wanqing Liao; Jianping Xu; et al. (Emerging Microbes and Infections, 2017)
Cases of tuberculosis/cryptococcosis co-infection are rapidly increasing in China. However, most studies addressing this co-infection have been published in Chinese journals, and this publication strategy has obscured this disease trend for scientists in other parts of the world. Our investigation found that 62.9% of all co-infection cases worldwide were reported in the Chinese population (n=197) between 1965 and 2016, and 56.3% of these Chinese cases were reported after 2010. Nearly all cases originated from the warm and wet monsoon regions of China. HIV-positive subjects tended to correlate with more severe manifestations of a tuberculosis/cryptococcosis co-infection than those without HIV. Notablely, dual tubercular/cryptococcal meningitis was the most frequent (54.0%) and most easily misdiagnosed (95.2%, n=40/42) co-infection. We also found that the combined use of cerebrospinal fluid pressure and concentrations of glucose, protein and chlorine might be an inexpensive and effective indicator to differentiate tubercular/cryptococcal co-infection meningitis from tubercular meningitis and cryptococcal meningitis.Emerging Microbes & Infections (2017) 6, e73; doi:10.1038/emi.2017.61; published online 23 August 2017